Using R for data analysis and research - Lillis, David (New Zealand Science Review, 2014)
​More than twenty years after its inception, the R statistics lan-guage and environment for scientific and statistical computing and graphics continues to be a New Zealand success story. In 2012, the total number of R users worldwide was estimated at about two million (ORACLE, 2012). The precise number of users around the world right now is unknown, but most probably the total number is considerably more than that of 2012, and growing rapidly.